Rekonstruksi Struktur Dayeuh Kerajaan Kendan - Maya Putri Rahayu; Weishaguna; Saraswati (UNISBA Press, 2022)
Abstract. The Kendan Kingdom is a part of the Tarumanegara Kingdom in West Java which was founded in the 6th century. Evidence the Kendan Kingdom is found in the form of artifacts, place naming, and parahyangan manuscripts. However, the spatial structure of the Kendan Kingdom has not been found, so to find out the spatial structure the author conducted a study with the aim of reconstructing the Kendan Kingdom Dayeuh structure based on artifacts, land characteristics, spatial hierarchy, and cosmological axis as an understanding of the meaning of some artifacts in Citaman Village and Kendan Village. This study uses the concept of land structure, the concept of a concentric hierarchy of mandalas, and the concept of the cosmological axis. The method used is a hermeneutic method with a comparative analysis method that is focused on comparing the Kendan Kingdom artifacts with data that have close characteristics, namely the Dayeuh Work of Galuh artifact which will later be validated by other supporting concepts. The analysis carried out will focus on discussing the analysis of the reconstruction of land structures, the analysis of the reconstruction of the mandala's concentric space hierarchy, and the analysis of the reconstruction of the cosmological axis. The results of the study show that the reconstruction of the Dayeuh space structure of the Kendan Kingdom forms the pattern of the Dayeuh structure which is interpreted with the uniqueness of being on a weak nirmalaning land, forming a hierarchical concentric pattern and forming a cosmological axis. Abstrak. Kerajaan Kendan merupakan salah satu bagian Kerajaan Tarumanegara di Jawa Barat yang berdiri pada abad ke-6. Bukti Kerajaan Kendan ini yaitu ditemukan dalam bentuk artefak, penamaan tempat, dan naskah parahyangan. Namun struktur ruang Kerajaan Kendan ini belum ditemukan, sehingga untuk mengetahui struktur ruang tersebut penulis melakukan studi dengan tujuan melakukan rekonstruksi struktur Dayeuh Kerajaan Kendan berdasarkan artefak, karakteristik lahan, hirarki ruang, dan poros kosmologi sebagai pemahaman arti dari beberapa artefak yang ada di Desa Citaman dan Desa Kendan. Studi ini menggunakan konsep struktur lahan, konsep hirarki konsentrik mandala, dan konsep poros kosmologi. Metode yang digunakan adalah metode hermeneutik dengan metode analisis komparasi yang difokuskan dengan cara membandingkan artefak Kerajaan Kendan dengan data yang memiliki kedekatan karakteristik yaitu artefak dayeuh Kerjaan Galuh yang nantinya divalidasi oleh konsep pendukung lainnya. Analisis yang dilakukan akan fokus membahas mengenai analisis rekonstruksi struktur lahan, analisis rekonstruksi hirarki ruang konsentrik mandala, dan analisis rekonstruksi poros kosmologi. Hasil studi menunjukkan rekonstruksi struktur ruang Dayeuh Kerajaan Kendan membentuk pola struktur Dayeuh yang diinterpretasikan dengan kekhasan terdapat pada lahan nirmalaning lemah, membentuk pola konsentrik berhirarki dan membentuk poros kosmologi.